Taxonomic position of Eothenomys wardi (Arvicolinae: Cricetidae) based on morphological and molecular analyses with a detailed description of the species - Zeng, Tao; Jin, Wei; Sun, Zhi Yu; Liu, Yang; Murphy, Robert W.; Fu, Jian Rong; Wang, Xin; Hou, Quan Fen; Tu, Fei Yun; Liao, Rui; Liu, Shao Ying; Yue, Bi Song (Zootaxa, 2013)
Ward’s Red-backed Vole (Eothenomys wardi) is a rodent from the family Cricetidae. This endemic species occurs only in extreme northwestern Yunnan province, China in the Mekong and Salween river divide. It occupies steep cliffs at 2,800 to 4,250 m above sea level on the remote Qinghai-Tibetan plateau. The validity of E. wardi is controversial and no spec-imens exist apart from the nominal series. In 2010, we collected 38 topotypes of E. wardi from Meri Snow Mountain. The results of our phylogenetic analyses based on nucleotide sequences of the mitochondrial genes cytochrome b (cytb) and cytochrome c oxidase subunit one (COI) suggest that E. wardi is the sister group of E. custos, against its previously pre-sumed sister species or conspecific species E. chinensis. In addition, seven out of 34 morphological characters differenti-ate E. wardi from other members of the genus Eothenomys. Therefore, we consider E. wardi to be a valid species and we provide its detailed morphological description.